The Role of Altered BDNF/TrkB Signaling in Amyotrophic Lateral Sclerosis - Pradhan, Jonu; Noakes, Peter G.; Bellingham, Mark C. (Frontiers in Cellular Neuroscience, 2019)
Brain Derived Neurotrophic Factor (BDNF) is well recognized for its neuroprotective functions, via activation of its high affinity receptor, tropomysin related kinase B (TrkB). In addition, BDNF/ TrkB neuroprotective functions can also be elicited indirectly via activation of adenosine 2A receptors (A2aRs), which in turn transactivates TrkB. Evidence suggests that alterations in BDNF/TrkB , including TrkB transactivation by A2aRs, can occur in several neurodegenerative diseases, including ALS. Although enhancing BDNF has been a major goal for protection of dying motor neurons (MNs), this has not been successful. Indeed, there is emerging in vitro and in vivo evidence suggesting that an upregulation of BDNF/TrkB can cause detrimental effects on MNs, making them more vulnerable to pathophysiological insults. For example, in amyotrophic lateral sclerosis (ALS), early synaptic hyper-excitability of MNs is thought to enhance BDNF-mediated signalling, thereby causing glutamate excitotoxicity, and ultimately MN death. Moreover, direct inhibition of TrkB and A2aRs has been shown to protect MNs from these pathophysiological insults, suggesting that modulation of BDNF/TrkB and/or A2aRs receptors may be important in early disease pathogenesis in ALS. This review highlights the relevance of pathophysiological actions of BDNF/TrkB under certain circumstances, so that manipulation of BDNF/TrkB and A2aRs may give rise to alternate neuroprotective therapeutic strategies in the treatment of neural diseases such as ALS.